Implementation of the One Family One Graduate Scholarship Program in Baznas of South Sumatera Province - Wiwik Oktarina; Fitri Oviyanti; Nazaruddin Nazaruddin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The background of this research stems from the researcher's interest in the privileges of zakat management institutions. The privilege is none other than that zakat management institutions are able to manage zakat effectively, especially in terms of maintaining the trust of the muzakki and are able to channel these funds through various programs, one of which is the Smart Sumsel program. Therefore, the researcher conducted a research entitled "Implementation of the One Family One Undergraduate Scholarship Program (SKSS) at BAZNAS, South Sumatra Province". This study aims to find out and analyze how the Implementation of the One Family One Undergraduate Scholarship Program is, as well as to determine the factors that influence the Implementation of the One Family One Undergraduate Scholarship Program (SKSS) at BAZNAS, South Sumatra Province. This study used descriptive qualitative method. Data collection techniques in the form of observation, interviews and documentation. Examination of the validity of the data is done by triangulation and combined with existing theory. Techniques of data analysis by means of data reduction, data presentation and drawing conclusions. The results of this study are: First, implementation is one element in management (management). Zakat management must be carried out optimally in order to achieve the goals/targets to be achieved as well as optimizing several programs that have been prepared and run at the BAZNAS institution of South Sumatra Province, one of which is the Smart Sumsel Program which is named SKSS. Second, the driving factor for the implementation of the SKSS scholarship at BAZNAS is one of the community's needs for a higher level of education because we already know that many children have had their education cut off due to low economic conditions. Meanwhile, the inhibiting factor of this implementation is the lack of muzakki who have paid zakat at the BAZNAS Institution so that the process of distributing ZIS funds is also limited. This is because there is no law that penalizes wealthy people who do not pay zakat.